Pelaksanaan Pemberian Bantuan Hukum Secara Cuma-Cuma Bagi Terdakwa Yang Tidak Mampu - Rahmat, Rahmat (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2022)
The aim of this research is to determine the optimization efforts carried out by the Legal Aid Office (Posbakum) at the Mamuju District Court in providing pro bono legal assistance to defendants, as well as to identify the challenges faced by legal advisors in providing pro bono legal assistance to defendants. This study falls under the category of empirical legal research, utilizing a socio-legal research approach, often referred to as